Disparities in cancer treatment among patients infected with the human immunodeficiency virus. Issue 15 (17th May 2016) - Suneja, Gita; Lin, Chun Chieh; Simard, Edgar P.; Han, Xuesong; Engels, Eric A.; Jemal, Ahmedin
Abstract : BACKGROUND: Patients with cancer who are infected with the human immunodeficiency virus (HIV) are less likely to receive cancer treatment compared with HIV‐uninfected individuals. However, to the authors' knowledge, the impact of insurance status and comorbidities is unknown. METHODS: Data from the National Cancer Data Base were used to study nonelderly adults diagnosed with several common cancers from 2003 to 2011. Cancer treatment was defined as chemotherapy, surgery, radiotherapy, or any combination during the first course of treatment. Multivariate logistic regression was used to examine associations between HIV status and lack of cancer treatment, and identify predictors for lack of treatment among HIV‐infected patients. RESULTS: A total of 10, 265 HIV‐infected and 2, 219, 232 HIV‐uninfected cases were included. In multivariate analysis, HIV‐infected patients with cancer were found to be more likely to lack cancer treatment for cancers of the head and neck (adjusted odds ratio [aOR], 1.48; 95% confidence interval [95% CI], 1.09‐2.01), upper gastrointestinal tract (aOR, 2.62; 95% CI, 2.04‐3.37), colorectum (aOR, 1.70; 95% CI, 1.17‐2.48), lung (aOR, 2.46; 95% CI, 2.19‐2.76), breast (aOR, 2.14; 95% CI, 1.16‐3.98), cervix (aOR, 2.81; 95% CI, 1.77‐4.45), prostate (aOR, 2.16; 95% CI, 1.69‐2.76), Hodgkin lymphoma (aOR, 1.92; 95% CI, 1.66‐2.22), and diffuse large B‐cell lymphoma (aOR, 1.82; 95% CI, 1.65‐2.00). Predictors of a lack of cancer treatment among HIV‐infected individuals varied by tumor type (solid tumor vs lymphoma), but black race and a lack of private insurance were found to be predictors for both groups. CONCLUSIONS: In the United States, HIV‐infected patients with cancer appear to be less likely to receive cancer treatment regardless of insurance and comorbidities. To the authors' knowledge, the current study is the largest study of cancer treatment in HIV‐infected patients with cancer in the United States and provides evidence of cancer treatment disparities even after controlling for differences with regard to insurance status and comorbidities. Further work should focus on addressing differential cancer treatment. Cancer 2016;122:2399–2407 . © 2016 American Cancer Society . Abstract : Human immunodeficiency virus (HIV)‐infected patients with cancer in the United States are less likely to receive cancer treatment compared with their uninfected counterparts, even after factoring in differences in insurance status and medical comorbidities. This disparity needs to be addressed as survival from HIV continues to improve and cancer becomes one of the leading causes of death in the HIV population.